KEBIMBANGAN IDENTITAS : SASTRA MUSLIM TURKI DAN SASTRA MUSLIM IMIGRAN DI EROPA DAN AMERIKA - Rahma Aulia; Reva Nur Alfiany; Ridwan Arief Rianaldi; Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
ABSTRACT This research explores the theme of identity ambiguity in literary works produced by Muslim writers from Turkey and Muslim immigrants in Europe and America, focusing on Muhammad Asad (“Road to Mecca”), Imamu Amiri Baraka (“Some Poems of Imamu Amiri Baraka”), and Abdulrazak Gurnah. These three authors describe their struggles in reconciling their Islamic identity with the different Western cultural environment. Asad through his narrative shows a complex spiritual transformation, attempting to find new meaning in Islam amidst a Western identity crisis. Baraka articulates African-American Muslim identity experiences in the context of political and social struggles, while Gurnah writes about diasporic experiences and postcolonial identity tensions. Important differences emerge when compared to non-Muslim works such as Washington Irving (“Alhambra”) who presents a romanticized narrative of Islam in the past, without internal identity struggles. Similarly, Annemarie Schimmel (“I am the Wind, You are the Fire”) focuses more on the mysticism and spirituality dimensions of Islam without centering on modern identity conflicts. This study concludes that the vacillation between two identities-Islam and the West-is a central theme in the works of Muslim writers, who present diverse approaches to spiritual, social and cultural issues in the modern world. Keywords: Literature, Identity, Muslim Literature, Balance. ABSTRAK Penelitian ini mengeksplorasi tema kebimbangan identitas dalam karya sastra yang dihasilkan oleh para penulis Muslim dari Turki dan imigran Muslim di Eropa dan Amerika, dengan fokus pada Muhammad Asad (